Ferromagnetic Fe-substituted Cerium Oxide Nanorods: Synthesis and characterization. (15th January 2017) - Alla, S.K.; Devarakonda, K.K.; Komarala, E.V.P.; Mandal, R.K.; Prasad, N.K.
Abstract: In this study, we have synthesized nanostructured Fex Ce1 − x O2 (0 ≤ x ≤ 0.5) particles by microwave refluxing method. All the samples were characterized using X-ray diffraction (XRD), transmission electron microscopy (TEM), Raman, UV–vis, photoluminescence and X-ray photoelectron spectroscopy. The microstructural characterization reveals that at lower concentration of Fe (x = 0.1), the sample predominantly has spherical shape particles along with nanorods. The nanorods become prominent with increased Fe content. Further, the substitution of Fe 3 + ions in CeO2 caused formation of defect states between Ce 4 + conduction band and O 2– valence band. These defect states or oxygen vacancies caused increase in the saturation magnetization (Ms ). Even the anisotropy of the nanorods reduces the localized antiferromagnetic interaction between Fe 3 + ions and hence MS value found to be increasing. Graphical abstract: Highlights: Nanorods of Fex Ce1-x O2 (0 ≤ x ≤ 0.5) samples were synthesized by single step microwave refluxing method. Addition of Fe facilitated the formation of nanorods. At higher concentration of Fe (x > 0.3), exhibits formation of α-Fe2 O3 phase indicating limited solubility of Fe. The samples exhibited ferromagnetic behavior and the saturation magnetization increases with increased Fe content.